Anti-inflammatory compounds reduce equine herpesvirus type 1 replication and cell-to-cell spread - Black, Jeanette B.; Frampton, Arthur R. (Frontiers in Veterinary Science, 2023)
Equine herpesvirus type 1 (EHV-1), is a highly transmissible pathogen that leads to a variety of clinical disease outcomes in the infected horse. One major sequela that may occur after EHV-1 infection is a neurological disease termed equine herpesvirus myeloencephalopathy (EHM). Clinical manifestations of EHM include fever, ataxia, incontinence, and partial to full paralysis, which may ultimately lead to the euthanization of the infected horse. To develop an effective treatment strategy for EHM, it is critical that the specific virus-host interactions that lead to EHM be investigated so that safe and effective therapeutic interventions can be developed and delivered. In this study, we examined the ability of four non-steroidal anti-inflammatory drugs (NSAIDS), one steroidal anti-inflammatory (dexamethasone), one Rho-Kinase (ROCK) inhibitor, and one JAK/STAT inhibitor (AG490) to reduce EHV-1 virus yields and cell to cell spread. We show that the NSAID, flunixin meglumine (FM), and the JAK/STAT inhibitor, AG490, significantly reduced virus yields in endothelial and epithelial cell lines and this inhibition was similar for two neurologic and two non-neurologic EHV-1 strains. In addition to reducing virus yields, AG490 and FM also significantly reduced the ability of EHV-1 to spread laterally from cell to cell.